(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
Word formation is one of the most important areas of linguistics that studies the creation of new words in a language. The continuous development of society, science, and technology requires languages to enrich their vocabularies. English and Uzbek employ various word-formation processes to create new lexical units and expand their lexicons. This article examines the major word-formation processes in English and Uzbek, including affixation, compounding, conversion, abbreviation, borrowing, and blending. The similarities and differences between the two languages are also analyzed from a comparative linguistic perspective.